Studi Korelasi Pendidikan dan Lama Kerja dengan Praktik Kolaborasi Interprofesi di Instalasi Gawat Darurat - Dwi Widyastuti; Rizky Aditya; Milkhatun Milkhatun (Fakultas Ilmu Kesehatan, 2023)
Interprofessional collaboration is the collaboration of healthcare professionals from different professional backgrounds with patients and their families to provide quality care. As for the implementation of collaborative practice, especially nurses, it can be influenced by education and years of service. Both of these can affect skills and abilities in taking action and being able to think critically and easily make decisions. The goal of this study was to determine the relationship between education and length of work of nurses with the practice of interprofessional collaboration in the emergency department. This study uses a quantitative method with a cross-sectional approach, which measures the independent variable (education and length of service) and the dependent variable (interprofessional collaboration practices) simultaneously. The results of the data obtained by nurses with D3 nursing education were 43 people (79.6%) and 11 nurses (20.4%), while for length of work ≤ 5 years 9 people (16.7%) and ≥ 5 years 45 people ( 83.4%). The results of the bivariate test using the Kendall Tau formula obtained a correlation coefficient of 0.715 and a p-value of 0.050. So it can be concluded that there is a relationship between education and length of work of nurses with the practice of interprofessional collaboration in the Emergency Room. There needs to be an increase in the further education level of nurses and clear policies and regulations are needed in carrying out inter-professional collaboration practices.